The INCREASE project: Intelligent Collections of food‐legume genetic resources for European agrofood systems. (23rd September 2021) - Bellucci, Elisa; Mario Aguilar, Orlando; Alseekh, Saleh; Bett, Kirstin; Brezeanu, Creola; Cook, Douglas; De la Rosa, Lucía; Delledonne, Massimo; Dostatny, Denise F.; Ferreira, Juan J.; Geffroy, Valérie; Ghitarrini, Sofia; et al.
SUMMARY: Food legumes are crucial for all agriculture‐related societal challenges, including climate change mitigation, agrobiodiversity conservation, sustainable agriculture, food security and human health. The transition to plant‐based diets, largely based on food legumes, could present major opportunities for adaptation and mitigation, generating significant co‐benefits for human health. The characterization, maintenance and exploitation of food‐legume genetic resources, to date largely unexploited, form the core development of both sustainable agriculture and a healthy food system. INCREASE will implement, on chickpea ( Cicer arietinum ), common bean ( Phaseolus vulgaris ), lentil ( Lens culinaris ) and lupin ( Lupinus albus and L. mutabilis ), a new approach to conserve, manage and characterize genetic resources. Intelligent Collections, consisting of nested core collections composed of single‐seed descent‐purified accessions (i.e., inbred lines), will be developed, exploiting germplasm available both from genebanks and on‐farm and subjected to different levels of genotypic and phenotypic characterization. Phenotyping and gene discovery activities will meet, via a participatory approach, the needs of various actors, including breeders, scientists, farmers and agri‐food and non‐food industries, exploiting also the power of massive metabolomics and transcriptomics and of artificial intelligence and smart tools. Moreover, INCREASE will test, with a citizen science experiment, an innovative system of conservation and use of genetic resources based on a decentralized approach for data management and dynamic conservation. By promoting the use of food legumes, improving their quality, adaptation and yield and boosting the competitiveness of the agriculture and food sector, the INCREASE strategy will have a major impact on economy and society and represents a case study of integrative and participatory approaches towards conservation and exploitation of crop genetic resources. Significance Statement: INCREASE, focusing on important food legumes, i.e., chickpea ( Cicer arietinum ), common bean ( Phaseolus vulgaris ), lentil ( Lens culinaris ) and lupin ( Lupinus albus and L. mutabilis ), develops new approaches to conserve, manage and characterize genetic resources. INCREASE is working with Intelligent Collections, consisting of nested core collections composed of single‐seed descent‐purified accessions, exploiting germplasm both from genebanks and on‐farm; these will be subjected to different levels of genotyping and phenotyping in order to meet, via a participatory approach, the needs of various actors, including breeders, scientists, farmers, citizen scientists and agri‐food and non‐food industries, including traits related to the value chain, to agroecosystem characteristics and to adaptation to climate change.